Determinan Loyalitas Nasabah pada Lembaga Keuangan Mikro Syariah di Kota Cirebon Jawa Barat - Indah Farikhah; Nur Eka Setiowati; Nining Wahyuningsih (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2025)
Abstract This study aims to analyze the effect of service quality, promotion, and trust on member loyalty at KPRI Harapan Sejahtera IAIN Syekh Nurjati Cirebon, both partially and simultaneously. The research uses a quantitative associative approach with data collected through questionnaires distributed to 95 respondents. The data were analyzed using multiple linear regression with SPSS version 27. The results show that partially, service quality, promotion, and trust have a positive and significant effect on member loyalty. Simultaneously, these three independent variables also significantly influence member loyalty, with a coefficient of determination (R²) of 0.665. This indicates that 66.5% of the loyalty variation is explained by these variables, while the remaining 33.5% is influenced by other factors. These findings emphasize the importance of service strategies, promotional efforts, and trust-building in strengthening member loyalty within cooperatives.